PEMBELAJARAN MENULIS KARYA ILMIAH MENGGUNAKAN DIMENSI BERNALAR KRITIS DENGAN MODEL PROJECT BASED LEARNING - Utrina, Annisa; Rustam; Wini, Lusia Oktri (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study's goal was to explain how students at SMAN 2 Sungai Penuh learned to write scientific papers using critical reasoning dimensions using a project-based learning model. The study's qualitative case study approach was used to collect data, which was then described descriptively through interviews, documentation studies, and observation.  The findings show that the teaching module, critical reasoning indicators, and the project-based learning model's phases are all used to effectively teach students how to write scientific articles utilizing critical reasoning dimensions. The findings of this study will be useful in helping the development of science by finding new theories to solve the problems faced by Indonesian language teachers.